Um espaço interdisciplinar de comunicação científica na Saúde coletiva: a revista Interface - Comunicação, Saúde, Educação - Cyrino, Antonio Pithon [UNESP]; Lima, Elizabeth Araújo; Garcia, Vera Lucia [UNESP]; Teixeira, Ricardo Rodrigues; Foresti, Miriam Celí Pimentel Porto [UNESP]; Schraiber, Lilia Blima (ABRASCO - Associação Brasileira de Saúde Coletiva, 2015)
This is a reflection upon 17 years of experience in the production of an interdisciplinary scientific journal, the publication “Interface: Communication, Health, Education,” whose scope is in the fields of Collective (Public) Health, Education and Communication. It also examines retrospectively the themes published by the journal, seeking to identify them in different sections of this publication. Finally, the evolution of the journal is analyzed.

Faz-se uma reflexão sobre a experiência de 17 anos de produção de periódico científico de natureza interdisciplinar, a revista “Interface: Comunicação, Saúde, Educação,” que tem como escopo os campos da Saúde Coletiva, da Educação e da Comunicação. Examina-se, também, retrospectivamente os temas publicados pelo periódico, buscando-se reconhecê-los nas diferentes seções desta publicação. Por fim, analisa-se o periódico em sua evolução.
An interdisciplinary space of scientific communication in Collective (Public) Health: the journal interface - Communication, Health, Education
Keywords: Public health; Scientific communication; Social and human sciences in health; Health professional education; Saúde coletiva; Comunicação científica; Ciências sociais e humanas em saúde; Formação de profissionais de saúde